Desenvolvimento de clones de cajazeiras sobre diferentes porta-enxertos e diversidade genética de acessos quanto a compostos bioativos nas cascas e folhas - Ramires, Christiane Mendes Cassimiro (Universidade Federal Rural do Semi-Árido, 2016)
The social and economic importance of yellow mombin is due to the marketing of its raw fruits and derivatives. The non-existence of commercial clones and the high plant size are the main obstacles to its rational cultivation being necessary to make the cloning a viable instrument through the interspecific rootstocks in order to downsize the plants heights. Studies done with yellow mombin grafted onto rootstocks of yellow mombin and hog-plum did not markedly downsize the plant height but these clones were not evaluated in other enviroments. The yellow mombin shows potential for remedies. In the pharmaceutical industry it is used as phytotherapics against the Herpes virus. In works done with this species some bioactive compounds were found in the leaves such as flavonoids and tannins. Although this potential, some researches on chemical characterization and genetic diversity among genotypes are incipient. The objective of this study was to evaluate the vegetative growth of yellow mombin clones grafted onto interspecific rootstocks in different environments and the genetic diversity as to bioactive compounds among accessions of the Emepa-PB´s germplasm bank. In order to evaluate the clones development two trials with a completely randomized block design were performed. The trial 1 was conducted in a 3 x 4 x 3 factorial design with four repetitions, totaling 36 treatments, being three different interspecific rootstocks with yellow mombin (S. mombin), hog-plum (S. tuberosa) and coarse mombin (S. venulosa), four graftings of yellow mombin clones (Itaitinga, Gereau, Lagoa Redonda and Genipabu) and three different places (João Pessoa, PB, Ipanguaçu, RN and Itabuna, BA). The trial 2 was conducted in a 4 x 3 factorial design, with four repetitions, totaling 12 treatments. Three graftings of yellow mombin (Emepa 8.2, Emepa 8.6 and Emepa 20) obtained from the grafting between yellow mombin clones, grafted onto yellow mombin, plus one genotype of ungrafted yellow mombin, were used in the same places. The evaluated variables for the two trials at the 8, 39 and 46 months old were plant height, stem circumference, crown spread, crown format, number of branches and percentage of dead plants. The conclusions are that the environment, the grafting and the rootstocks did not influence the size and vigor of the clones allowing the identification of the morphological characteristics variations in each environment; that in Trial 1, for the three enviroments, the graftings of yellow mombin onto yellow mombin, hog-plum and coarse mombin rootstocks did not form clones with ideal sizes so that they cannot be recommended for commercial plantation; that in Trial 2, in the three enviroments, the Emepa 8.2 showed smaller size, bigger crown spread, major number of branches, 100% crown in a spread format and it can be recommended for new studies and later multiplication for commercial plantation. Leaves and barks of 27 yellow mombin accessions of the Emepa´s germplasm bank, in João Pessoa, PB, were used. The extractions were performed with methanol and the identification and quantification of bioactive compounds were checked through the High-Performance Liquid Chromatography (HPLC). For the grouping of accessions were used the Principal Components Analysis (PCA) and the UPGMA method. The standardized Euclidean distancewas used as a measure of genetic diversity. Rutin, quercetin, ellagic acid and geraniin compounds were quantified in leaves and ellagic acid and geraniin compounds were quantified inbarks. The highest amounts were found in leaves. Seven groups were formed. The accession group A3 was the most divergent with high amounts of rutin, quercetin and ellagic acid in leaves. The conclusion is that there is variability among accessions and it must be preserved and exploited through the genetic improvement programs
Development of yellow mombin clones onto different rootstocks and diversity of genetic accessions as to the bioactive compounds in the bark and leaves
Keywords: Porta-enxerto interespecífico; Clones copa; Variabilidade genética; Ácido elágico; Rutina; Quercetina; Geraniina; Interspecific rootstock; Scion clones; Genetic variability; Rutin; Quercetin; Ellagic acid; Geraniin; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA